Contribution of Conflict Materials in the Subject of Local History of the Demak Kingdom For Historical Awareness of Grade XI IIS 2 Students of Sultan Agung 2 Islamic High School Jepara - Khubaib, Abdurahman; Atmaja, Hamdan Tri; Sodiq, Ibnu (Universitas Negeri Semarang, 2020)
This research aims to (1) know and analyze the effect of conflict material history learning in the study of local history of Demak Kingdom student awareness toward history and (2) students’ appreciation toward the material. The research method used is qualitative type research with a descriptive strategy. The source of data comes from informants, learning activities, and documents. Data collection techniques include observation techniques, interviews, and documentation. The result of this study was summarized into two major points that showed that (1) history learning using local sub-materials of local history contributed toward history awareness level. By studying conflicts that had happened in Demak Kingdom, students could prevent them from happening again in the future, and (2) student appreciation toward the material that related to their environment was positive.